Царьград. Тайный путь - Посняков Андрей Анатольевич (Лениздат, 2009)
Экземпляры: ф.21 (2009) / Инвентарный номер: 52616 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 62 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445